KORELASI ANTARA POLIGAMI, TASAWWUF FALSAFI, DAN IRFANI - Awaliyah Musgamy (AN-NISA, 2018)
The key to the permanence of marital ties, both monogamy and polygamy, is of course due to the foundation of love. However, if the nature of this love is based solely on the spouse or mere happiness of the world, it is only natural that a dispute occurs. The concept of philosophical Sufism and the theory of Irfani teach that the basis of marriage should be to anchor that holy love to the Supreme Love, in the fusion of self and ego to mortal towards Him. So even in polygamy, everyone in the family will not do it because they expect other praise. But all choices and blessings are imprinted only on the Divine of God.